ANTICUERPOS CONTRA EL VIRUS CAUSANTE DE LA RINOTRAQUEITIS INFECCIOSA EN VACUNOSDE LA PROVINCIA DE MELGAR, PUNO - Pariente A., Edgar (2012)
The prevalence of bovine herpesvirus type 1 (BHV-1) was determined in 382 bovine older than 6months of age in herds of the province ofMelgar, Puno, Peru. Serum samples were tested for antibodies against BHV-1 using the viral neutralization test. The 29.0 ± 0.1%(110/382) of the samples had antibodies against BHV-1, without differences between young (2 years old) and mature (³2 years old) animals.Antibody titers varied between 2 to 128. The results indicated that BHV-1 infection is widespread in cattle population of the province ofMelgar, Puno, and it is possibly contributing to cause respiratory disease problems in young animals.